Your country still needs you... - Sargent Russell, Jill (World Today)
The article discusses the need for modern states to have plans for mass mobilization in preparation for war. Topics covered include the necessity of conscription in the British and U.S. traditions, the importance of planning in modern warfare, and the role of a wider range of technical and other skills in forming the basis of selection as economic sectors are incorporated into defence. Also mentioned is the need for computer and network-savvy personnel due to the rise of cyber warfare.